Microstructure of ultrafine graded cemented carbides with cubic rich surface - CHEN Jian; HUANG Yi-ping; ZHU Rui; ZHOU Li; DENG Xin; WU Shang-hua; LIU Bing-yao (Fenmo yejin jishu)
The microstructure and mechanical properties of the WC‒10TiC‒0.5VC‒0.5Cr2C3‒12Co and WC‒12Co cemented carbides in the functionally graded and uniform structure were systematically investigated by sintering in nitrogen-rich atmosphere. The scanning electron microscope (SEM), energy disperse spectroscope (EDS), and X-ray diffractometer (XRD) were used for the microstructure observation and phase composition analysis, and the hardness and fracture toughness tests were made in both the surface and the center of the cemented carbides. The results show that, different from the WC‒12Co cemented carbides in uniform structure, the surface layer of the WC‒10TiC‒0.5VC‒0.5Cr2C3‒12Co cemented carbides in the gradient structure is rich in TiCN cubic phase, which is about 12 μm in thickness, and there is a cobalt-rich and coarse-grain intermediate layer below the surface layer of the WC‒10TiC‒0.5VC‒0.5Cr2C3‒12Co cemented carbides. Such gradient and ultrafine cemented carbides show the advantage as the high hardness in the surface layer, the high fracture toughness in the core, and the ultrafine and uniform WC grain.